Perioperative blood transfusion is a predictor of acute and chronic renal function deterioration after partial and radical nephrectomy for renal cell carcinoma - Mühlbauer, Julia; Gilde, Johannes de; Müller-Steinhardt, Michael; Porubský, Štefan; Walach, Margarete; Nuhn, Philipp; Klüter, Harald; Wagener, Nina; Kriegmair, Maximilian (Urologia internationalis, 2020)
Introduction: The aim was to evaluate the impact of perioperative blood transfusions (PBTs) on renal function after surgery for renal cell carcinoma (RCC). Methods: Consecutive patients with RCC who underwent partial nephrectomy or radical nephrectomy between 2005 and 2015 at a tertiary care center were included. Minimum follow-up period was 6 months. A PBT was defined as the transfusion of packed erythrocyte concentrate (EC) within 7 days before until 30 days after surgery. The multivariable analyses were carried out by Cox regression. Results: The overall cohort included 851 patients, of whom 93 (10.9%) received a PBT. The median follow-up was 46 months (range 28-72). In case of a PBT, a median of 2 EC was transfused. PBT patients were older and had a poorer performance status and more comorbidities as well as locally more advanced or metastatic tumors. In the multivariable analyses, PBT was an independent prognostic factor for acute as well as chronic renal impairment (hazard ratio (HR) 2.72, 95% confidence interval (95% CI) 1.45-5.10, p = 0.002 and HR 2.23, 95% CI 1.26-3.70, p = 0.007). Conclusion: PBT is associated with acute and chronic deterioration of kidney function after surgery for RCC. Thus, it may be used to identify patients requiring close nephrological monitoring.
Online publiziert: 28. Juli 2020
Gesehen am 05.01.2026